Surface engineering of polymeric biomaterials. - Vladkova, Todorka G. (Smithers Rapra, 2012)
Biomaterials work in contact with living matter and this gives a number of specific requirements for their surface properties, such as bioinertness or bioactivity, antibiofouling, and so on. Surface engineering based on physical, chemical, physical-chemical, biochemical or biological principles is important for the preparation of biomaterials with the desired biocontact properties. This book helps the reader gain the knowledge to enable them to work in such a rapidly developing area, with a comprehensive list of references given for each chapter. Strategies for tailoring the biological respons.